Co-creating Virtual Reality Interventions for Alcohol Prevention: Living Lab vs. Co-design - Dietrich, Timo; Guldager, Julie Dalgaard; Lyk, Patricia; Vallentin-Holbech, Lotte; Rundle-Thiele, Sharyn; Majgaard, Gunver; Stock, Christiane (Frontiers in Public Health, 2021)
Addressing the need for collaborative involvement in health intervention design requires application of processes that researchers and practitioners can apply confidently to actively involve end-users and wider stakeholder groups. Co-creation enables participation by focusing on empowering a range of stakeholders with opportunities to influence the final intervention design. While collaboration with users and stakeholders during intervention design processes are considered vital, clear articulation of procedures and considerations for various co-creation methodologies warrants further research attention. This paper is based on two case studies conducted in Australia and Denmark where researchers co-created virtual reality interventions in an alcohol prevention context. This paper explored and reflected on two co-creation methods–co-design and the Living Lab—and showcased the different processes and procedures of each approach. The study demonstrates that both approaches have merit, yet highlights tensions in distinguishing between the application of each of the respective steps undertaken in each of the processes. While a lot of similarities exist between approaches, differences are evident. Overall, it can be said that the Living Lab is broader in scope and processes applied within the Living Labs approach are more abstract. The co-design process that we applied in the first case study is described more granularly delivering a clear a step-by-step guide that practitioners can implement to co-design solutions that end-users value and that stakeholders support. An agenda to guide future research is outlined challenging researchers to identify the most effective co-creation approach.